Strength and dilatancy of coral sand in the South China Sea - Wang, Xing; Wu, Yongxin; Lu, Yi; Cui, Jie; Wang, Xinzhi; Zhu, Changqi (Bulletin of engineering geology and the environment, 2021)
To clarify the effects of compactness and stress level on the strength and deformation characteristics of coral sand in the reclaimed foundation of island reefs in the South China Sea, consolidated-drained triaxial shear tests were conducted on coral sand with four different relative densities under a constant confining pressure range. Brittleness index and dilatancy coefficient were introduced to quantitatively express the strain softening and dilatancy characteristics of coral sand. The results showed that when σ 3 ′ was between 150 and 300 kPa, the strain softening and dilatancy characteristics of coral sand decreased with increasing effective confining pressure and decreasing compactness. Brittleness index and dilatancy coefficient exhibited a good linear relationship with effective confining pressure and relative density, respectively. The peak friction angle and dilatancy angle of coral medium sand both decreased with increasing effective confining pressure and decreasing relative density. Based on this behavior, the attenuation amplitudes of peak friction angles of medium dense and dense coral medium sand with increasing confining pressure logarithm were determined. The critical-state friction angle of coral medium sand was determined based on Bolton’s stress–dilatancy relationship. The relational expressions of peak friction angle/relative dilatancy index with mean effective stress and relative density were established, respectively.